A CASE OF COMBINING FOLLICULAR CYSTS OF THE LOWER JAW WITH ERUPTION CYSTS IN A CHILD - Tkachenko, P.I.; Bilokon, S.O.; Dolenko, O.B.; Starchenko, I.I.; Korotych, N.N.; Popelo, Yu.V.; Lokhmatova, N.M. (World of Medicine and Biology, 2024)
The literature describes clinical cases combining follicular cysts of the jaws with other pathological processes. We performed a clinical and morphological analysis of a case of a combination of bilateral follicular cysts of the lower jaw with eruption cysts in a 7-year-old patient. The final clinical diagnosis is follicular cysts of the lower jaw from the 36th and 46th teeth and eruption cysts in the lateral parts of the lower jaw in the 36th and 46th teeth. Cystostomy was performed on the patient. At the same time, 75 and 85 teeth were left in the tooth rows, partially exposed crowns of 36 and 46 teeth. We did not find any peculiarities in the morphological picture of the postoperative material. At the same time, an eruption cyst that occurs above an erupting tooth does not lead to the appearance of a defect in the form of bone cavities, but the hydraulic pressure of its contents inhibits the tooth's eruption. However, it should not be forgotten that the variety of combinations of jaw cysts, particularly follicular cysts, with other pathology of the jaw bones requires a balanced, differentiated, individualized approach to diagnostic measures, treatment, and rehabilitation tactics for each patient.
Keywords: children; jaws; odontogenic cysts; follicular cysts; cystostomy